Partitioning Displacement Demand of Flexible-base Structures because of SSI. Issue 3 (17th February 2022) - Karatzetzou, Anna; Pitilakis, Dimitris; Stefanidou, Sotiria
ABSTRACT: Due to soil -structure-interaction (SSI), the seismic lateral structural deformations may be substantially different from the ones traditionally calculated from the fixed-base structure on free-field approach. Additionally, the actual displacements of foundations considering soil compliance are of practical interest in some applications. In the present study, seismic elastic displacement demand of compliant coupled soil- structure (SFS) systems, is investigated through numerical time history analyses. The numerical displacement demand is validated through an analytical solution, comparison between FEM and analytical solution is provided and finally, a practical, simplified approach for displacement evaluation is proposed. The displacements are presented in terms of dimensionless parameters such as soil to structure stiffness ratio 1/σ and slenderness ratio h/B, while closed-form relationships are proposed.